THE INFLUENCE OF LEADERSHIP STYLE, MOTIVATION, COMPENSATION, WORK ENVIRONMENT, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Aufa Nadia Basyir; Ida Farida (The Asia Pacific Journal Of Management Studies, 2024)
This research aims to analyze and determine the influence of leadership style, motivation, compensation, work environment and job satisfaction on employee performance at PT. YYY The population used in this research were employees of PT. YYY. The sampling technique used is non-probability sampling with purposive sampling, namely taking samples with consideration according to the desired criteria. The sample in this research consisted of 105 employees. The data collection technique uses a questionnaire. Based on the results of hypothesis testing data analysis, it shows that leadership style has an effect on employee performance, motivation has no effect on employee performance, compensation has an effect on employee performance, the work environment has an effect on employee performance and job satisfaction has no effect on employee performance.